THE IMPACT OF ZONATION SYSTEM POLICY IN THE PPDB ON STUDENTS' OBTAINING AT SMA NEGERI 8 SURABAYA - Idawati Idawati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research was conducted by using a descriptive method with a quantitative approach. The quantitative approach was chosen to be tested theories by examining and measuring variables in the form of relationships, differences, influences, contributions, and the others. The research was carried out by describing the students acquisition data on the new student admission (PPDB) using zoning system based on the academic year 2019-2020 and the student acquisition data on the academic year PPDB 2018-2019 as a comparison. Based on the results of the study, the new students of PPDB using zoning system was considered lower in terms of economic and educational background of parents. There were more parents with less education (elementary & junior high school) in the zoning system than in the rayon system, whereas parents with higher education in the zoning system were fewer than the rayon system.  Likewise, in terms of income, there were more people with the low income in the zoning system than in the rayon system, and those having high income were fewer than in the rayon system. The study showed that the intelligence and the result of National Examination Score (NUN) in the zoning system is lower than in the rayon system. The intelligent level of the students in the zoning system is mostly dominated by the scores under 90-109, while in the rayon system were dominated by the scores above 90-109.  The National Examination Scores (NUN) in the zoning system were evenly distributed from a range of scores 0 to 30, while in the rayon system the scores were dominated by a range of scores 28-30, with the lowest score 24.